Improving Indonesian Speaking Skills for Thai Students Through Role Play Techniques - Anwar Rasyid; Syamsuyurnita Syamsuyurnita (MASI Mandiri Edukasi, 2026)
Indonesian speaking skills among Thai junior high school students remain relatively low due to limited opportunities for active and contextual oral practice in the classroom. This study aims to improve the Indonesian speaking skills of Thai students through the application of role-play techniques. The research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The subjects were 22 students of the Matayum 1 class, equivalent to grade VII in Indonesia. The research was conducted in two cycles, each consisting of two meetings. Data were collected through speaking skill tests, observations, and documentation. Speaking performance was assessed based on fluency, pronunciation, vocabulary, sentence structure, and speaking confidence. The results showed a significant improvement in students’ speaking skills, with the average score increasing from 62.4 in the pre-cycle to 72.1 in cycle I and 82.7 in cycle II. Additionally, the implementation of role play techniques enhanced students’ activeness, confidence, and ability to use Indonesian communicatively and contextually. Therefore, role play techniques are proven effective in improving Indonesian speaking skills for foreign learners at the junior high school level.